2008
DOI: 10.1097/iae.0b013e318158eca4
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence From the Outer Retina and Subretinal Space

Abstract: The physical separation of the retinal outer segments from the retinal pigment epithelium hinders proper phagocytosis of the outer segments. Accumulation of the shed but not phagocytized outer segments plays a role in disease manifestations for a number of macular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
123
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(134 citation statements)
references
References 68 publications
6
123
0
5
Order By: Relevance
“…23 The progression of OCT and fundus autofluorescence findings in central serous retinopathy were described by Spaide. 26 It was suggested that elongation of photoreceptor outer segments result in progressive hyperautofluorescence. With time autofluorescence becomes granular, possibly due to macrophage accumulation on the surface of the outer retina and in the subretinal space.…”
Section: Discussionmentioning
confidence: 99%
“…23 The progression of OCT and fundus autofluorescence findings in central serous retinopathy were described by Spaide. 26 It was suggested that elongation of photoreceptor outer segments result in progressive hyperautofluorescence. With time autofluorescence becomes granular, possibly due to macrophage accumulation on the surface of the outer retina and in the subretinal space.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the intense autofluorescence at wavelengths similar to that used for detection of RPE lipofuscin, the composition of the yellow vitelliform material in cuticular drusen has been proposed to contain retinoids derived from shed outer segments of the photoreceptors. 8 By analogy, the intensely autofluorescent material in association with subretinal drusenoid deposits suggests the presence of retinoids as well.…”
Section: Discussionmentioning
confidence: 99%
“…In cuticular drusen, subretinal fluid has been seen in some cases, which along with the presumed accumulation of outer segments, and may suggest abnormal RPE function. 8 The simple presence of subretinal fluid has been associated with the accumulation of yellow highly autofluorescent material in a number of diseases ranging from central serous chorioretinopathy to vitelliform macular dystrophy. [8][9][10] Accumulation of autofluorescent material because of defective phagocytosis occurs in the RCS rat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usefulness of FAF was reported in various retinal diseases including Stargardt's disease and Best's disease. [5][6][7] In this report, we examined fundus leopard spots in a case with uveal effusion syndrome by simultaneous imaging by FA, ICGA, FAF and spectral domain optical coherence tomography (SD-OCT). The procedure enabled us to identify the exact characteristics of leopard spots in SD-OCT and FAF imaging.…”
Section: Introductionmentioning
confidence: 99%